Independent and interactive effects of a top and an intermediate fish species on the food web structure of a tropical stream - Motta, R. L.; Uieda, V. S. [UNESP] (Springer Nature, 2008)
Two fish species, one top predator (Imparfinis mirini) and one intermediate detritivorous species (Hisonotus depres-sicauda), were experimentally manipulated to evaluate their relative importance in structuring the periphytic community, as well as their effects on the other trophic levels. An enclosure experiment was conducted in the Potreirinho creek, a second order tributary of Paranapanema River, SE Brazil. Five treatments were used: enclosure of the predator species, enclosure of the detritivorous species, enclosure of both together, exclusion of all fish species (closed control cage), and cage open to all fish community (open control). Through direct and indirect effects, I. mirini, when alone, gave rise to a trophic cascade that resulted in a positive effect on algal resources. Through direct effects, H. depressicauda, when alone, reduced the amount of organic matter, resulting in a positive indirect effect on algae. In addition, when the two species were enclosed together, only the effects determined by the detritivorous species were present. The results indicate the important role of the intermediate detritivorous species in the maintenance of the composition and trophic structure of the analyzed community by reducing the effects caused by the top predator. © 2008 Akadémiai Kiadó.
Keywords: Experimental manipulation; Indirect effects; Macroinvertebrates; Predation; Strong effects; Trophic cascade; Trophic levels